PENGGUNAAN MEDIA DIORAMA UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA PADA MATERI HARMONI DALAM EKOSISTEM MATA PELAJARAN IPAS KELAS V SEKOLAH DASAR NEGERI 153/X HARAPAN MAKMUR - Eka Rosmawati; Indryani; Ugi Nugraha; Urip Sulistiyo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Learning at Sekolah Dasar Negeri 153/X Harapan Makmur, Tanjung Jabung Timur Regency, is still conducted conventionally using media that focus solely on the fifth-grade integrated science textbook (IPAS V). This has resulted in low student motivation and learning outcomes. This study aims to analyze the improvement of student motivation and learning outcomes through the application of diorama media The research design employed was a true experimental design with a pre-test post-test control group model. The study population included all fifth-grade students, consisting of two classes, Va and Vb. A sample of 24 students was selected, comprising 14 students in the control class and 10 students in the experimental class. Data were collected using observation sheets to measure learning motivation and multiple-choice tests to assess learning outcomes. Data analysis was conducted using percentage calculations and statistical tests The research results revealed a significant increase in learning motivation in the experimental class compared to the control class. In the experimental class, students' motivation during the first meeting reached 77.5% (very good category) and increased to 91.25% (very good category) in the second meeting. Conversely, in the control class, students' motivation was only 40% (fair category) in the first meeting, rising to 50% (fair category) in the second meeting. The learning outcomes also demonstrated a significant difference between the experimental and control classes. In the experimental class, the average pre-test score of 30.4 increased to 71 in the post-test, with an N-gain of 0.61, classified as a medium category. Meanwhile, in the control class, the average pre-test score of 32.14 increased to 53.64 in the post-test, with an N-gain of 0.34, also classified as a medium category. The hypothesis test results showed that the \( t_{calculated} = 11.9 \) exceeded \( t_{table} = 2.07 \) (df = 22, α = 0.05), leading to the rejection of \( H_0 \) and acceptance of \( H_a \).In conclusion, there is a significant difference in student motivation and learning outcomes between those taught using diorama media and those taught conventionally in the ecosystem topic for fifth-grade students at Sekolah Dasar Negeri 153/X Harapan Makmur, Tanjung Jabung Timur Regency. Diorama media effectively enhances both student motivation and learning outcomes.